Rapid and effective treatment of traumatic spinal cord injury using stem cell derived exosomes - Jiafu Mu; Jiahe Wu; Jian Cao; Teng Ma; Liming Li; Shiqing Feng; Jianqing Gao (Elsevier, 2021)
Traumatic spinal cord injury is a fatal acute event without effective clinical therapies. Following the trauma, immediate neural protection and microenvironment mitigation are vitally important for nerve tissue repair, where stem cell-based therapies could be eclipsed by the deficiency of cells due to the hostile microenvironment as well as the transport and preservation processes. Effective emergency strategies are required to be convenient, biocompatible, and stable. Herein, we assess an emergency cell-free treatment using mesenchymal stem cell-derived exosomes, which have proven capable of comprehensive mitigation of the inhibitory lesion microenvironment. The clinically validated fibrin glue is utilized to encapsulate the exosomes and in-situ gelates in transected rat spinal cords to provide a substrate for exosome delivery as well as nerve tissue growth. The emergency treatment alleviates the inflammatory and oxidative microenvironment, inducing effective nerve tissue repair and functional recovery. The therapy presents a promising strategy for effective emergency treatment of central nervous system trauma.